PERANCANGAN RESORT DENGAN PENDEKATAN ARSITEKTUR TROPIS DI PESISIR DANAU MOAT BOLAANG MONGONDOW TIMUR SULAWESI UTARA - Deisy Pontolawokang; Debbie A. J. Harimu; Threesje A. N. Harimu (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2023)
This design aims to design a resort on the shores of Lake Mo'oat Boltim, to meet the needs of tourists with a tropical architectural approach. Tourists visiting Boltim in the last 3 years have increased by ± 52.5% per year, it is estimated that in the next 5 years the number of tourists visiting will be ± 700,000 tourists [5]. Site area is 37,756 m2, KDB 40% = 15,103 m2 KDH 60% = 22,654 m2. The climatic conditions at this tropical site are humid with quite large amplitudes of temperature during the day and night with average daytime temperature of 31℃ and an average night time of 20℃ with humidity of ± 80%. The average rainfall is 502.4 mm [1]. The resort classification is a three-star resort with a total of 30 rooms, supporting facilities including ballrooms, praying room, restaurants, meeting rooms and other facilities [2]. The steps taken in the design process are data collection, through surveys, observations, measurements, conducting comparative studies of the same object, while the analysis technique used is strengths and weaknesses analysis then synthesis takes into account opportunities and threats. Strengths are described as potentials, while weaknesses are architectural constraints in responding to design needs. The synthesis takes into account aspects of compatibility with tropical architectural concepts, aesthetics, economy, functionality and implementation possibilities [6]. This design concludes that the concept of the shape of the building is taken from the analogy of the boat metaphor, the circulation pattern in the main building is a grid system, the supporting facilities use a linear circulation pattern while in the outer space it uses a dispersed circulation pattern so that visitors can explore visiting all existing facilities. The tropical architectural concept that is implemented is in the form of: (1) The shape of the roof with a wide canopy and an angle of 450 from the analogy of a boat sail to cope with high rainfall (2) Wide openings for cross ventilation, (3) A large garden to reduce environmental temperature at noon. (4) Buildings are hollow to remove moisture from the ground. (5) Wooden construction to create a natural and tropical impression can also warm the room temperature at night.